2021
DOI: 10.3389/fpsyt.2021.657322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Childhood Obesity and Psychological Factors on Sleep

Abstract: The aim of the study was to analyze sleep duration and behaviors in relation to psychological parameters in children and adolescents with obesity seeking inpatient weight-loss treatment in comparison to normal-weight children, and whether or not these variables would improve during the time course of treatment. Sixty children or adolescents with overweight and obesity (OBE) and 27 normal-weight (NW) peers (age: 9–17) were assessed for subjective sleep measures through self-reported and parent-reported question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(66 reference statements)
0
4
1
Order By: Relevance
“…In contrast, a systematic review and meta-analysis by Moradi et al observed no association between childhood adiposity and childhood anxiety (Moradi et al, 2022). Several other studies have suggested inconsistent associations between childhood obesity and childhood anxiety, but no studies have reported a protective association (Godina-Flores et al, 2022, Mazurak et al, 2021. Therefore, further validation of our findings in an independent study is warrented.…”
Section: Discussioncontrasting
confidence: 72%
“…In contrast, a systematic review and meta-analysis by Moradi et al observed no association between childhood adiposity and childhood anxiety (Moradi et al, 2022). Several other studies have suggested inconsistent associations between childhood obesity and childhood anxiety, but no studies have reported a protective association (Godina-Flores et al, 2022, Mazurak et al, 2021. Therefore, further validation of our findings in an independent study is warrented.…”
Section: Discussioncontrasting
confidence: 72%
“…20 It is also a risk factor for sleep disturbances in overweight children, and both obesity and depression are associated with the presence of high inflammatory impacts. 21,22 It is also shown that children who are obese may also have multiple psychosocial challenges, 12 may be subject to weight-based cyber victimization that potentially provokes depression, 23 plus poor academic as well as coping skills that can duly impact their overall mental and physical health significantly and adversely. 24 They may also be at risk for excess overweight status due to excess or poor eating practices as a result of being cared for by depressed caregivers, 17 and that could that well foster signs of negative psychological outcomes such as depression, low self-esteem, and life quality among these youth in their own right.…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing prevalence of obesity in children, a majority of studies have focused on the contributing role of sleep deficiency to obesity [ 96 ]. However, research also reports that obese adolescents experienced considerably poorer sleep outcomes (i.e., duration, quality, and daytime somnolence) than their peers of normal weight [ 12 ]. The exact underlying mechanisms are unclear but involve those at the biological and environmental levels (e.g., dietary intake, media use, physical activity) [ 12 ].…”
Section: Nutrition Dietary Intake and Weightmentioning
confidence: 99%
“…However, research also reports that obese adolescents experienced considerably poorer sleep outcomes (i.e., duration, quality, and daytime somnolence) than their peers of normal weight [ 12 ]. The exact underlying mechanisms are unclear but involve those at the biological and environmental levels (e.g., dietary intake, media use, physical activity) [ 12 ]. Further research should clarify the direction of the relationship between sleep and obesity.…”
Section: Nutrition Dietary Intake and Weightmentioning
confidence: 99%
See 1 more Smart Citation